Support System In Determining Engine Oil For Matic Motorcycles Using AHP Method - Ratih Adinda Destari; Asbon Hendra Azhar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Most of our society at this time do not fully understand how to choose the best engine oil for their automatic motorcycle. People prefer engine oil based on recommendations from motorcycle manufacturers or just by looking at well-known brands and do not understand the characteristics and types of engine oil. The results obtained by choosing the wrong engine oil can experience a decrease in performance on the automatic motorcycle engine used. So to overcome this, public knowledge is needed about the engine oil criteria which is a priority consideration in choosing engine oil and facilitates the selection process so that it does not require a long time in the selection. By using the Analytical Hierarchy Process (AHP) method and with data collection techniques using observations, interviews, questionnaires and literature studies, it can help the community in selecting the appropriate engine oil for the type of automatic vehicle they use every day. From this research, the results obtained are Federal Matic occupies the first priority with a weight of 0.0969, Enduro Matic with a weight of 0.0883, AHM-Oil MPX 2 with a priority with a weight of 0.0876, Yamalube Super Matic with a weight of 0.0841 , Shell - Advance AX7 Matic on the 5th priority with a weight of 0.0751 and TOP 1 Action Matic on the 6th priority with a weight of 0.0679